PENEGAKAN HUKUM TERHADAP WARGA NEGARA ASING YANG MENYALAHGUNAKAN IZIN KEIMIGRASIAN YANG SAH - Fernando Yongky Ambat; Tri Sulistyowati (Reformasi Hukum Trisakti, 2021)
Every foreigner who enters Indonesian territory must have an immigration permit. Immigration permits for foreign nationals are issued by Immigration Officials based on the results of examinations on foreigners who will enter Indonesian territory through the Immigration Checkpoints (TPI), people who abuse immigration permits are included in immigration violations as happened in the case of the Sukabumi District Court Decision Number 98/Pid.Sus/2021. The problems are how did the immigration crime by Echendu Michael Chinda occur in Indonesia, and whether law enforcement for the immigration crime committed by Echendu Michael Chinda was in accordance with Law-No. 6 of 2011 concerning immigration. The answers to the two main issues above are obtained in a juridical-normative manner which is descriptive in nature based on secondary data which is analyzed qualitatively by drawing conclusions using deductive logic.